Long-Term Levels of LDL-C and Cognitive Function: The CARDIA Study. (10th November 2021) - Mefford, Matthew T.; Chen, Ligong; Lewis, Cora E.; Muntner, Paul; Sidney, Stephen; Launer, Lenore J.; Monda, Keri L.; Ruzza, Andrea; Kassahun, Helina; Rosenson, Robert S.; Carson, April P.
Abstract: Objectives: It is uncertain if long-term levels of low-density lipoprotein-cholesterol (LDL-C) affect cognition in middle age. We examined the association of LDL-C levels over 25 years with cognitive function in a prospective cohort of black and white US adults. Methods: Lipids were measured at baseline (1985–1986; age: 18–30 years) and at serial examinations conducted over 25 years. Time-averaged cumulative LDL-C was calculated using the area under the curve for 3, 328 participants with ≥3 LDL-C measurements and a cognitive function assessment. Cognitive function was assessed at the Year 25 examination with the Digit Symbol Substitution Test [DSST], Rey Auditory Visual Learning Test [RAVLT], and Stroop Test. A brain magnetic resonance imaging (MRI) sub-study ( N = 707) was also completed at Year 25 to assess abnormal white matter tissue volume (AWMV) and gray matter cerebral blood flow volume (GM-CBFV) as secondary outcomes. Results: There were 15.6%, 32.9%, 28.9%, and 22.6% participants with time-averaged cumulative LDL-C <100 mg/dL, 101–129 mg/dL, 130–159 mg/dL, and ≥160 mg/dL, respectively. Standardized differences in all cognitive function test scores ranged from 0.16 SD lower to 0.09 SD higher across time-averaged LDL-C categories in comparison to those with LDL-C < 100 mg/dL. After covariate adjustment, participants with higher versus lower time-averaged LDL-C had a lower RAVLT score ( p -trend = 0.02) but no differences were present for DSST, Stroop Test, AWMV, or GM-CBFV. Conclusion: Cumulative LDL-C was associated with small differences in memory, as assessed by RAVLT scores, but not other cognitive or brain MRI measures over 25 years of follow-up.